Efektivitas Penggunaan Media PowerPoint terhadap Hasil Belajar Kognitif Siswa Kelas V dalam Mata Pelajaran IPAS - Ilham Esa Tiffani; Agnita Siska Pramasdyahsari; Sumarno; Mulyani (UNIB Press, 2024)
In the field of teaching and learning, the use of digital media, especially PowerPoint, is still rarely implemented by teachers. Therefore, the development of PowerPoint media is needed to ensure that the learning process runs optimally and achieves the desired learning objectives. The purpose of this research is to determine the effectiveness of using PowerPoint media on the cognitive learning outcomes of fifth-grade students in the IPAS subject. This research method employs quantitative research. The sampling technique used in this study is saturation sampling. The results of the PowerPoint media research are based on different tests using non-parametric statistical testing with the Wilcoxon formula to obtain student learning data, showing differences before and after the use of PowerPoint media.